Dual-polarized HF antenna - Yee, Sheng Jie (2019)
The final year project is to study the integration of a vertical polarized antenna, which will be conical monopole, and a horizontal polarized antenna, which is bow-tie dipole. Dual polarization will be attained with the combination of both antennas. Both antennas are in the frequency range of 3 to 30 MHz, which is known as High Frequency (HF). Miniaturization techniques are explored to reduce the height of the conical monopole and the height and width of the bow-tie dipole (biconical antenna). ANYSS High Frequency Structure Simulator (HFSS) will be used to design and simulate the antenna, which simulation of both antennas will be tested individually and after integrating. HFSS can simulate full wave electromagnetic in 3-D field solver as it uses Finite Element Method (FEM). It is a software widely used in RF/microwave design (e.g. Antenna design and platform integration, Filters and waveguide structures). It can achieve essential parameters which includes S-Parameters (S11), Voltage Standing Wave Ratio (VSWR) and displays radiation patterns of gain. They will serve as important features to determine the optimum parameters of the antenna.